LOGICAL FALLACIES IN COMMUNICATION AND UNDERSTANDING LANGUAGE PRECISION - Taterao Bapurao Nikalje (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the age of the digital era, it becomes more and more difficult to understand how to communicate with each other. Due to the prism of communicative logical fallacies, this essay identifies the cause of the phenomenon and its outcomes. An analysis of such mistakes and that these mistakes significantly impact on the way one understands things indicates the essential essence of accuracy in logical reasoning in effective communication, as it is shown in the present paper. With introduction of digital mediums and ease of transferring information, the way we built up and expressed the ideas has taken a new twist. Through all this information, there is confusion and miscommunication among people owing to the fallacies of logic like jumping into conclusion, functions of ad hominen and false dichotomies. The usage of these fallacies in your writing is not good basically since it is likely to cause you difficulty in understanding and comprehension simply because it is likely to cloud your thinking and in the process make your words not that clear. As though that is not enough, these fallacies lower the level of a conversation and a publicly conducted debate. They contribute to the fragmentation of the society and disinformation by lowering the standard of critical thinking and closing the avenue to quality dialogue. In order to be able to perform effective communication process, it is necessary to detect logical fallacies and correct them. The reason is that there is a need to accept the fact that individuals may make one another more intelligible and reduce the number of misunderstandings when they promote the use of consistent and reasonable words. Such an active position turns the society a bit more literate and socially active, capable of responding to complex situations with a clear and understandable reaction, and it also establishes personal communication skills.